A Novel Class of Multiferroic Material, Bi4Ti3O12·nBiFeO3 with Localized Magnetic Ordering Evaluated from Their Single Crystals. (6th December 2016) - Zhao, Hongyang; Cai, Kang; Cheng, Zhenxiang; Jia, Tingting; Kimura, Hideo; Ma, Zhibin; Fu, Qiuming; Huang, Zhideng; Matsumoto, Takao; Tohei, Tetsuya; Shibata, Naoya; Ikuhara, Yuichi
Abstract : Novel multiferroic materials have attracted increasing attention in recent years. Aurivillius bismuth‐layer structured Bi4 Ti3 O12 · n BiFeO3 (BTFO: n = 1–3, 5) compounds with potential multiferroic properties are such a compound. However, the data on these BTFOs are ambigious, inconsistent, and incomplete. Therefore BTFOs were grown into single crystals for a systematic evaluation. Their crystal structures and microstructures show that intergrowth of layer structure occurs easily in this class of material. Their ferroelectric measurements show strong anisotropy and dielectric peaks at high temperature, accompanied by an abnormal loss that corresponds to their polar phase transition. At room temperature, ferroelectric hysteresis loops were successfully measured; the loops show a strong dependence in their polarization and coercive field on different values of n and anisotropy. Magnetic measurement shows that all the single crystals display magnetic transitions at high temperatures and weak ferromagnetism at room temperature. Electron spin resonance (ESR) results show the coexistence of ferromagnetic and paramagnetic signal components in all the compounds. Scanning probe microscope measurements show magnetic domains switched together with electric domains by use of an electric field. Therefore we conclude that overall spin disorder with localized order is the character of this class of material, with observed magnetoelectric (ME) coupling. This work could also point the way to novel multiferroic materials in locally magnetic ordered systems. Abstract : A multiferroic single crystal contains overall spin disordering with localized order, and magnetoelectric coupling. Four layers of (Bi3 Ti4 O13 ) 2− are sandwiched by two closely stacked Bi layers. Between the two closely stacked Bi layers five Ti(Fe)O6 layers can be clearly recognized. In a larger area, the evolution of the Ti(Fe)O6 layers indicates that intergrowth occurs easily in this class of material.